2021
DOI: 10.1029/2020ja027873
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Dynamical Complexities in Geospace as Captured by Dst Over Four Solar Cycles 1964–2008.

Abstract: Geospace refers to the region of the outer space near Earth; this includes the upper atmosphere, ionosphere as well as the magnetosphere. Geospace basically span through region of space which goes from the solar photosphere to the mesosphere of the Earth. The studies of the dynamics of geospace has continued to attract attention due to its significant impact on the present day space-dependent technological operations. Today, health and functionality of thousands of satellites domiciled in space environment, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…The fractal dimension changeability suggests substantial differences in the level of storm complexity. Comparable results were obtained recently by [24,74], showing that during major geomagnetic storms the strongest nonlinearity features occur. Moreover, there is no unequivocal dependence of the fractal dimension extremes on the maximum value of the Kp-index, as most of the storms shown in Figure 6a-f, were characterized by the maximum value of Kp = 8+.…”
Section: Katz Fractal Dimension Of Geoelectric Fieldsupporting
confidence: 83%
See 1 more Smart Citation
“…The fractal dimension changeability suggests substantial differences in the level of storm complexity. Comparable results were obtained recently by [24,74], showing that during major geomagnetic storms the strongest nonlinearity features occur. Moreover, there is no unequivocal dependence of the fractal dimension extremes on the maximum value of the Kp-index, as most of the storms shown in Figure 6a-f, were characterized by the maximum value of Kp = 8+.…”
Section: Katz Fractal Dimension Of Geoelectric Fieldsupporting
confidence: 83%
“…As it was suggested in [12], based on power spectrum and Kolmogorov entropy analyses, the state of the magnetospheric response described by the AE-index was chaotic during the storm of January 1983. This result was confirmed recently by [24], when four chaos quantifiers and the multifractality approach were used in the analysis of the Dst-index data over the four solar cycles 20-23.…”
Section: Fractal Time Seriessupporting
confidence: 72%
“…This is due to the mixing of gases, coupling between different layers, and several driving forces acting differently across the layers of geospace. It has been shown that chaotic dynamics exist in the magnetosphere [18], stratosphere [48], mesosphere [49], and ionosphere [19]. The implication of chaotic dynamics in geospace is that long-term prediction of the system is difficult.…”
Section: Complex Measuresmentioning
confidence: 99%
“…It is negative, zero, and positive for dissipative, conservative, and chaotic systems, respectively. This approach has been used in many fields, including atmospheric physics and geospace [18]. Chaos theory has been used to investigate nonlinear processes in the ionosphere in different regions of the world [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Wavelet-leader multifractal analysis of magnetospheric dissipations, as measured by the AL index, reveal that the magnetosphere is a multi-scale, complex, turbulent system, driven into a non-equilibrium self-organized state, which may explain the observations of repeatable and coherent substorm phenomena with underlying complex multifractal behavior in the plasma sheet (Valdivia et al 2013). The interaction of the solar wind with the Earth's magnetosphere also contributes for multifractality in measurements of the geomagnetic activity, such as the geomagnetic induced current (Wirsing & Mili 2020) and the Dst index (Ogunjo et al 2021), although internal sources of multifractality must also be considered, as Gopinath (2016) suggests that multifractality of the auroral electrojet index is fairly independent of the solar activity cycle. Wawrzaszek et al (2019) characterized multifractality in intermittent turbulence of heliospheric magnetic field fluctuations from Ulysses spacecraft, concluding that intermittency/multifractality decreases with heliospheric distance, a result that was confirmed by Kiran et al (2021).…”
Section: Introductionmentioning
confidence: 96%